Induksi Keragaman Genetik pada Tanaman Alocasia Menggunakan Mutagen Kimia Kolkisin - Fitri Damayanti; Zakiah Fithah A’ini (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Alocasia green velvet (neon taro) is one of the ornamental plants that plant lovers hunt. The increasing standard of living and interest in beauty and uniqueness, the demand for this plant has increased. This provides an opportunity for ornamental plant farmers to develop the potential of Alocasia. Genetic diversity in Alocasia is very low because generally these plants are propagated such as vegetative. Therefore, it is necessary to increase genetic diversity so that new types of Alocasia are produced with more attractive leaf shapes, sizes, and coloration. Efforts that can be applied are mutation induction using a chemical mutagen, namely colchicine. The plant material was used that the tuber of the Alocasia plant. The study was conducted using a randomized block design with two factors, the colchicine concentration (0, 10, 15, 20, 25, and 30 mgL-1) and the immersion time (1 and 2 days). The 30 mgL-1 colchicine treatment gave better growth: producing the highest number of leaves, the longest root length, the highest number of shoots and the percentage of sprouting tubers that reached 100%. Colchicine treatment of 10 mgL-1 with immersion time of 1 day resulted in a different leaf shape. Colchicine treatments of 10, 15, 20, and 25 mgL-1 produced plants with younger leaf coloration than the control. As well as the 30 mgL-1 colchicine treatment produced vigorous plants with larger stem sizes.